Diagnostic values of serum cathepsin B and D in patients with nasopharyngeal carcinoma. Issue 1 (December 2016) - Tan, Gongjun; Liu, Qianxu; Tang, Xiaowei; Kang, Ting; Li, Yuejin; Lu, Jinping; Zhao, Xiaoming; Tang, Faqing
Abstract Background The diagnostic and prognostic significance of increased cathepsin B (CTSB) and cathepsin D (CTSD) concentration in the serum of cancer patients were evaluated for some tumor types. High expression of CTSD and CTSB was detected in biopsy tissues from nasopharyngeal carcinoma (NPC). However, whether CTSD and CTSB serve as diagnostic and prognostic markers of NPC remains unclear. Methods Serum samples were collected from 40 healthy volunteers and 80 NPC patients enrolled in the study. CTSB and CTSD in the serum samples were detected using enzyme-linked immunosorbent assay (ELISA). Concomitantly, the relationship between CTSB and CTSD concentrations and clinicopathological prognosis was assessed. The sensitivity and specificity of the two components in the diagnosis of NPC were evaluated in 80 NPC patients. Results ELISA analysis showed that in the sera obtained from NPC patients, the CTSB concentration was 12.5 ± 3.5 mg/L (median, 12.4 mg/L), and the CTSD concentration was 15.7 ± 8.7 mg/L (median, 14.7 mg/L). CTSB and CTSD levels were significantly higher in the NPC patient population compared to the healthy control population (p  = 0.001;p  = 0.001, respectively). The presence of CTSB and CTSD in the serum of the patients with NPC correlated with the tumor node metastasis (TNM) scores (p  = 0.001). Other parameters were not identified to be of significance. Receiver operating characteristic (ROC) analysis showed that a cut off CTSB concentration of 12.4 mg/L had 61.9 % sensitivity and 63.2 % specificity in the prediction of progression-free survival (Area under the curve (AUC) = 0.525; 95 % CI, 39.7–65.2;p  = 0.704); whereas a cut off CTSD concentration of 14.7 mg/L had 66.7 % sensitivity, and 58.5 % specificity (AUC = 0.552; 95 % CI, 42.3–68.1;p  = 0.42). Conclusions Serum CTSB and CTSD concentrations were found to have a diagnostic value in NPC. However, the CTSB and CTSD serum levels had no prognostic role for the outcome in NPC patients.